CD38/cADPR Signaling Pathway in Airway Disease: Regulatory Mechanisms - Deepak A. Deshpande; Alonso G. P. Guedes; Richard Graeff; Soner Dogan; Subbaya Subramanian; Timothy F. Walseth; Mathur S. Kannan (Mediators of Inflammation, 2018)
Asthma is an inflammatory disease in which proinflammatory cytokines have a role in inducing abnormalities of airway smooth muscle function and in the development of airway hyperresponsiveness. Inflammatory cytokines alter calcium (Ca2+) signaling and contractility of airway smooth muscle, which results in nonspecific airway hyperresponsiveness to agonists. In this context, Ca2+ regulatory mechanisms in airway smooth muscle and changes in these regulatory mechanisms encompass a major component of airway hyperresponsiveness. Although dynamic Ca2+ regulation is complex, phospholipase C/inositol tris-phosphate (PLC/IP3) and CD38-cyclic ADP-ribose (CD38/cADPR) are two major pathways mediating agonist-induced Ca2+ regulation in airway smooth muscle. Altered CD38 expression or enhanced cyclic ADP-ribosyl cyclase activity associated with CD38 contributes to human pathologies such as asthma, neoplasia, and neuroimmune diseases. This review is focused on investigations on the role of CD38-cyclic ADP-ribose signaling in airway smooth muscle in the context of transcriptional and posttranscriptional regulation of CD38 expression. The specific roles of transcription factors NF-kB and AP-1 in the transcriptional regulation of CD38 expression and of miRNAs miR-140-3p and miR-708 in the posttranscriptional regulation and the underlying mechanisms of such regulation are discussed.